PEMBEBASAN BERSYARAT SEBAGAI HASIL UPAYA PEMBINAAN NARAPIDANA TITIPAN DI RUTAN KELAS II A SAMARINDA - Husain, M. (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTProvision of parole to inmates is the last link in the effort of fostering prisoners in the prison system. By means of parole, inmates can improve communication with the wider community, rediscover their self-esteem as human beings and their existence as members of the community. In this conditional implementation must be considered or based on correctional principles, one of which states that during the loss of freedom of movement, prisoners must be introduced to the community and should not be alienated from it. Factors that are obstacles or barriers to the implementation of parole are as follows: The prisoner in question still has other cases that have not been decided by the court; The prisoner in question has not received remission or legal deduction; Recidivist inmates; The convict in question while being fostered in the Detention Center violates; Prisoners who undergo their sentence are less than one year; The detention officer indeed wants the parole to be increased, but the prisoner often commits violations while in the detention center, so that the administrative requirements do not support prisoners being sent to parole; Even from society, parole sometimes gets obstacles that make prisoners often feel unacceptable, for example the victim's family is still grudging against the prisoners concerned and there is an assumption from the public that these prisoners after leaving and getting parole can disrupt order and security in the environment his place.